EFFECT SPRAYING SOME MICRONUTRIENTS AND ADD HUMIC ACID IN TRAITS OF ROOTS AND LEAVES CONTENT OF NUTRIENTS IN GREEN BEANS - & Al-JUMAILI, Al-DULAIMI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was carried out at the research station of the Agriculture College - of Baghdad University for two seasons, spring and autumn 2015, Using hybrid seeds, primal, one of the early Cultivars. To study the effect of iron, zinc spray and add organic nutrient for the vegetative growth and plant yield of green beans. The experiment was conducted using factorial experiment (4×3) with in randomized complete block designe with three replicates and12 treatments resulting from interaction spray four treatments (0, 0.5 Zn ml L-1, 2g Fe L-1 and 0.5 Zn ml L-1+ 2g Fe L-1) and add three levels of humic acid (0, 2 and 3) kg ha-1, after melted in a calculated amount of water and insert into the groove around the plants per experimental unit. The results showed the superiority of the treatment (M3H2) humic acid 3g.ha-1 and iron 2g.L-1 it the highest length of the roots (38.76 cm. Plant-1 ) for spring season, while superiority treatment (M4H2) Humic acid 3g.ha-1 elemental iron, zinc length of the root amounted 29.20 cm .Plant-1 for autumn season, highest weight of dry roots (6.49 and 4.34 q. plant-1), superiority treatment M4H2 in highest concentration of iron and zinc in leaves amounted (264.67, 236) mg. kg-1 and (43.00, 46.30) mg kg-1 dry mater seasons of spring and autumn on respectively. Superiority the treatment of M4H2 significantly by giving highest percentage of nitrogen, phosphorus and potassium in leaves (2.40, 2.19), (0.40, 0.42) and (2.73, 2.77)% for two seasons, spring and autumn respectively.